Topping influences crop photosynthesis and alters the absorption and redistribution of nutrients: a case study of tobacco - Shi, Nuo; Yao, Heng; Wang, Ge; Zhao, Gaokun; Wu, Yuping; Zhang, Guanghai; Kong, Guanghui; Wang, Na; Bai, Yuxiang; Du, Yu; Zi, Dingchun; Zhang, Limei; et al. (Frontiers in Plant Science, 2025)
Topping eliminates apical dominance in tobacco, enhancing the quality of the upper leaves. However, the mechanisms by which topping influences photosynthesis and the leaf structure, and regulation of chemical composition remain unclear. This study investigated the regulatory mechanisms of different topping periods (buttoning, budding, first flower, and full flower topping and without topping) on photosynthesis, the leaf structure, and the chemical composition in tobacco by integrating photosynthetic physiology, anatomical, and chemical composition analyses. The results indicated that topping makes the leaves thinner, promotes leaf lamina opening, and results in thicker mesophyll, compact palisade tissue, and loose spongy tissue. It can also significantly enhance photosynthetic capacity. The contents of total sugar, reducing sugar, and K2O content increased significantly, while the content of chloride ions decreased significantly. The contents of total nitrogen and nicotine were moderate. In conclusion, topping promotes leaf lamina opening, enhances photosynthesis, and associated with changes in the chemical composition of tobacco leaves. Additionally, this study aims to provide a theoretical basis for the promotion of tobacco topping techniques.